Dairy Products Benets in Lowering Blood Pressure - Michelle Martina; Daniela Angeline (Cermin Dunia Kedokteran, 2020)
Hypertension is one of the risk factor leading to cardiovascular disease. Diet plays an important role for preventing hypertension and maintaining blood pressure. One of the dietary approaches includes intake of daily consumption of low fat dairy product. This review will discuss the relationship between daily dairy intake and blood pressure. Hipertensi merupakan salah satu faktor risiko penyakit kardiovaskular. Selain terapi medikamentosa, nutrisi berperan penting dalam mencegah hipertensi dan menjaga tekanan darah. Salah satu pendekatan nutrisi pada pasien hipertensi mencakup konsumsi produk susu rendah lemak. Ulasan ini membahas hubungan konsumsi produk susu dengan tekanan darah.